Comparative efficacy of grouting and mixing methods for stabilizing collapsible soils with nano-clay and cement - Mostafa Zamanian; Meghdad Payan; Mahdi Salimi; Fatemeh Qahremani; Mahyar Arabani; Mohammad Mahdi Shalchian (Case Studies in Construction Materials)
Collapsible soils, characterized by sudden settlement upon wetting, pose significant geotechnical challenges for infrastructure foundations. While conventional stabilization methods exist, their effectiveness is often limited by non-uniform treatment or environmental concerns. This study systematically evaluates two innovative approaches—permeation grouting and mechanical mixing—using nano-clay (NC) and ordinary Portland cement (OPC) to stabilize such problematic soils. Through comprehensive laboratory experiments, undisturbed soil samples were treated with varying concentrations of NC (0.05–0.25 wt%) and OPC (0.5–2.5 wt%), followed by mechanical testing and microstructural analysis. The mechanical behavior of treated soils was evaluated through direct shear tests on both reconstituted samples and undisturbed samples taken from the centers and sides of grouted specimens at various curing times. Key results show that NC grouting (with the optimal concentration of 0.1 wt%) achieved fairly uniform strength improvement, increasing cohesion from 4 kPa to 35.8 kPa and internal friction angle from 26° to 36.5° after 28 days. In contrast, OPC grouting improved only the central zones (cohesion: 44 kPa at 2.5 wt%), while side specimens showed limited gains (≤14 kPa) due to pore clogging. The mixing method proved ineffective as a soil improvement strategy, particularly for NC-mixed specimens. The study establishes NC permeation grouting as a sustainable and efficient alternative to conventional methods, offering superior spatial consistency with only one-tenth the material requirement of cement-based approaches. It provides both mechanistic insights and practical solutions for collapsible soil stabilization, advancing the field through its novel application of nanomaterial injection technology.